A history of the animal world in the ancient Near East - Collins, Billie Jean (Brill, 2002)
This title concerns man's contact with the animal world: sacrifice, sacred animals, diet, and domestication. Chapters on art, literature, religion and animal husbandry reveal a picture of the complex relationships between the peoples of the Ancient Near East and (their) animals.
Keywords: Human-animal relationships -- Middle East.; Animals in art.; Animals in literature.; Animals -- Religious aspects.; Animals in the Bible.; Relations homme-animal -- Moyen-Orient.; Animaux dans l'art.; Animaux dans la littérature.; Animaux -- Aspect religieux.; Animaux dans la Bible.; SOCIAL SCIENCE -- Human Geography.; Animals in art; Animals in literature; Animals in the Bible; Animals -- Religious aspects; Human-animal relationships; Middle East; Altertum; Tierdarstellung; Tiere; Alter Orient; Naher Osten; Relation homme-animal.; Thème artistique.; Animal.; Thème littéraire.; Aspect religieux.; Antiquité; Moyen-Orient.; Samfundsvidenskab -- Sociologi.